(untitled) (Journal of Information and Communication Technology, 2024)
Addressing dyslexia through digital product design presents distinct challenges and necessitates the development of tailored strategies or guidelines to facilitate children in reading accurately and efficiently. Hence, a design guideline was formulated by integrating Interaction Design (IxD) principles to enhance comprehension and minimise reading errors while using digital applications. Nonetheless, the existing design guidelines for dyslexia people have yet to be confirmed and updated to cater to the current and latest five IxD dimensions. Therefore, this paper presents an eye-tracking usability test that was conducted to identify usability issues pertaining to the design guideline by performing the test on an application called BacaDisleksia, which was developed based on the existing guideline. A usability test was conducted using the Tobii eye-tracking tool through an in-person and moderated session with six dyslexic children. The test reveals pertinent design issues by analysing heat maps and gaze plots. Based on these findings, this paper proposes a refined design guideline with five IxD dimensions and strategies conducive to dyslexia-friendly application design by incorporating space and time components. The results contribute to the development of comprehensive design guideline for people with dyslexia, which aligns with UNESCO’s objective of utilising technology to promote inclusion for disabled learners. This effort underscores the significance of informed design decisions in digital innovation for better-serving individuals with dyslexia and similar learning challenges.